2020
DOI: 10.2196/16817
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Psychologists' Attitudes Toward Internet Interventions: Exploratory Cross-Sectional Study

Abstract: Background Despite the significant body of evidence on the efficacy and cost-effectiveness of internet interventions, the implementation of such programs in Portugal is virtually non-existent. In addition, Portuguese psychologists’ use and their attitudes towards such interventions is largely unknown. Objective The aim of this study was to explore Portuguese psychologists’ knowledge, training, use and attitudes towards internet interventions; to investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 55 publications
9
55
0
1
Order By: Relevance
“…These results reproduce those by Mendes-Santos (2020), in which only 29.6% of the inquired Portuguese psychologists admitted to having used digital technologies in their professional practice. The results of the present study also showed that most Portuguese psychologists had never or rarely used digital technologies as a means of delivering psychological counseling and therapy before the COVID-19 pandemic [ 6 ]. There is also a high degree of similarity between the tools most frequently used in our study and the tools used, the resources that psychologists most recommend to their clients (e.g., telephone calls, e-mails, video conferences, social networks, and apps) [ 6 ], and the most used devices (e.g., computers and smart phones) reported in other research (e.g., [ 14 ]).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…These results reproduce those by Mendes-Santos (2020), in which only 29.6% of the inquired Portuguese psychologists admitted to having used digital technologies in their professional practice. The results of the present study also showed that most Portuguese psychologists had never or rarely used digital technologies as a means of delivering psychological counseling and therapy before the COVID-19 pandemic [ 6 ]. There is also a high degree of similarity between the tools most frequently used in our study and the tools used, the resources that psychologists most recommend to their clients (e.g., telephone calls, e-mails, video conferences, social networks, and apps) [ 6 ], and the most used devices (e.g., computers and smart phones) reported in other research (e.g., [ 14 ]).…”
Section: Discussionmentioning
confidence: 67%
“…In several countries, an increasing number of studies have also sought to characterize the attitudes of psychologists toward the inclusion of ICTs in their professional practice and to gather evidence about the efficacy and effectiveness of psychological interventions mediated by ICTs (e.g., [ 7 , 16 , 17 , 18 , 19 , 20 , 21 ]). Regarding the psychologists’ attitudes, the results of the studies are not consistent (e.g., [ 6 , 22 ]). In Portugal, a recent study assessing psychologists’ attitudes revealed a slightly negative/neutral position regarding internet interventions and greater acceptability of blended treatment interventions when compared to standalone internet interventions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations